Speech Acts Directive in Dialogues in the English Textbook: A Pragmatic Analysis - Ayu Safitri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article explores the use of directive speech acts in dialogues presented in English textbooks. Drawing on the theoretical framework of speech act theory by Parker and Riley (1994), the study focuses on understanding how directives—utterances that seek to influence the behavior of the listener—are presented in various dialogues. It examines the various forms and functions of directives, their role in communication, and how they help learners of English understand and practice practical conversational strategies. The article highlights the importance of directive speech acts in both formal and informal contexts, with specific examples drawn from English language textbooks. This study uses qualitative descriptive research where data is found in dialogues in textbooks and then matched with theory and poured into a sentence. This study found that there are five types of directive speech acts, namely, orders, warnings, giving advice, suggestions, and recommendations. In this study, 7 command data, 3 warning data, 2 advice data, 8 suggestion data, and 1 recommendation data were found. In this study, two techniques were found in the delivery of speech acts, namely direct and non-direct. Non-direct techniques tend to contain an element of politeness rather than direct. In addition, the speech actions in this textbook can help students understand, and using directive speech acts effectively can significantly improve communicative competence in language learners.